Inovasi Media Digital dalam Pembelajaran STEAM untuk Meningkatkan Kreativitas dan Kolaborasi Siswa di Sekolah Dasar Berbasis IB PYP - Rossa Triyantara, Dendy; Khamidi, Amrozi; Karwanto, Karwanto; Kristanto, Andi; Sayhidul Haq, Mohammad (Jurnal Pendidikan : Riset dan Konseptual, 2026)
This research aims to analyze the utilization of digital media in STEAM learning to enhance students' creativity and collaboration in IB PYP-based Elementary Schools. STEAM learning emphasizes the integration of science, technology, engineering, arts, and mathematics through a project-based approach, while the IB PYP curriculum emphasizes inquiry-based learning and active student engagement. The research method employs a systematic-qualitative literature study by examining 40 relevant sources including books, journal articles, and policy documents published between 2010 and 2025. The study findings indicate that digital media plays a multidimensional role as a tool for concept representation, design platform, collaboration medium, and creative production facility that aligns with IB PYP principles. Digital media can enhance creativity through open-ended tasks and multimodal exploration with appropriate pedagogical scaffolding support. In the collaboration aspect, digital platforms facilitate synchronous and asynchronous group work, but require the development of digital social skills. Implementation challenges include infrastructure limitations, access gaps, and varying teacher readiness. Research recommendations emphasize the importance of developing professional learning communities, data-based piloting approaches, and learning design that holistically integrates pedagogy and technology to optimize the development of students' 21st-century skills.